Effect of High Selective Serotonin-Reuptake Inhibitor Doses on the Development and Treatment of Sarcoid-Like Reaction - Badr Rashed Al-Ghamdi (Case Reports in Medicine)
Sarcoidosis is a systemic disorder characterized by the presence of noncaseating granulomas that are most commonly observed in the lungs. Sarcoid-like reaction has been reported to develop in response to several immune modulator agents and antidepressants. In this report, a case of pulmonary sarcoidosis that was strongly related to the use of more than the average recommended dose of selective serotonin-reuptake inhibitor (SSRI) medications has been described. The patient, a 37-year-old, single, Caucasian woman, who suffered from severe depression and who presented to the emergency department with shortness of breath, low-grade fever, a dry cough, fatigue, and the loss of appetite, was diagnosed with this condition, and she failed to respond to the administered sarcoidosis treatment until the SSRI medications that she was using were discontinued; furthermore, she relapsed when one of these medications was reintroduced. Based on these observations, we were able to show a possible relationship between sarcoid-like reaction and SSRIs, and therefore, in the case of patients with interstitial lung diseases who are using SSRIs, we recommend that meticulous precautions be taken while planning their treatment and careful follow-ups be implemented to monitor their progress.